The effects of 8 weeks of creatine monohydrate and glutamine supplementation on body composition and performance measures - Lehmkuhl, M.; Malone, M.; Justice, B.; Trone, G.; Pistilli, E.; Vinci, D.; Haff, E. E.; Kilgore, J. L. (The Journal of Strength and Conditioning Research, 2003)
Twenty-nine (17 men, 12 women) collegiate track and field athletes were randomly divided into a creatine monohydrate (CM, n = 10) group, creatine monohydrate and glutamine (CG, n = 10) group, or placebo (P, n = 9) group. The CM group received 0.3 g creatine;pdkg body mass per day for 1 week, followed by 0.03 g creatine;pdkg body mass per day for 7 weeks. The CG group received the same creatine dosage scheme as the CM group plus 4 g glutamine;pdday 1. All 3 treatment groups participated in an identical periodized strength and conditioning program during preseason training. Body composition, vertical jump, and cycle performances were tested before (T1) and after (T2) the 8-week supplementation period. Body mass and lean body mass (LBM) increased at a greater rate for the CM and CG groups, compared with the P treatment. Additionally, the CM and CG groups exhibited significantly greater improvement in initial rate of power production, compared with the placebo treatment. These results suggest CM and CG significantly increase body mass, LBM, and initial rate of power production during multiple cycle ergometer bouts.